2010
DOI: 10.26719/2010.16.8.831
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and associated factors of persistent diarrhoea in Iranian children admitted to a paediatric hospital

Abstract: To identify the frequency and associated factors of persistent diarrhoea in a paediatric hospital in Tehran, Islamic Republic of Iran, children admitted with acute diarrhoea were followed prospectively until resolution of the episode. Persistent diarrhoea developed in 19.6% of the 424 diarrhoea cases. Children with persistent diarrhoea were significantly younger than those with acute diarrhoea (15.3 versus 29.4 months). Enteroaggregative Escherichia coli was the most prevalent pathogen in both groups, but othe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
13
0
8

Year Published

2010
2010
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(22 citation statements)
references
References 13 publications
0
13
0
8
Order By: Relevance
“…The most prevalent strains identified included atypical enteropathogenic E. coli (EPEC), followed by enteroaggregative E. coli (EAEC). EPEC has emerged as an important pathogen in outbreaks of acute diarrhoea in developed [58] and developing countries [59,60] and both EPEC and EAEC infections are dangerous in immunocompromised individuals and children [61][62][63]. A study by Traore et al [5] on some of the rivers in the Venda region detected several pathogenic strains of E. coli, such as enteroinvasive E. coli (EIEC), enterotoxigenic E. coli (ETEC), and enteropathogenic E. coli (EPEC), which are strains that are known for causing diarrhoea in children [24] and that was also detected in this study.…”
Section: Prevalence Of Pathogensmentioning
confidence: 99%
“…The most prevalent strains identified included atypical enteropathogenic E. coli (EPEC), followed by enteroaggregative E. coli (EAEC). EPEC has emerged as an important pathogen in outbreaks of acute diarrhoea in developed [58] and developing countries [59,60] and both EPEC and EAEC infections are dangerous in immunocompromised individuals and children [61][62][63]. A study by Traore et al [5] on some of the rivers in the Venda region detected several pathogenic strains of E. coli, such as enteroinvasive E. coli (EIEC), enterotoxigenic E. coli (ETEC), and enteropathogenic E. coli (EPEC), which are strains that are known for causing diarrhoea in children [24] and that was also detected in this study.…”
Section: Prevalence Of Pathogensmentioning
confidence: 99%
“…Since that, sporadic and outbreaks of acute and persistent diarrhea in different parts of the world (developing and developed countries) have been reported. [5][6][7][8][9][10] Ahangarzadeh-Rezaee M, et al, J Anal Res Clin Med, 2015, 3 To investigate the prevalence of enteroaggregative Escherichia coli (EAEC) in children < 10 years with a diagnosis of gastroenteritis by multiplex polymerase chain reaction (MPCR).…”
mentioning
confidence: 99%
“…Rota virus antigen obtained from stool of AGE cases between 15-47% of hospitalized children with AGE, just in 12% of controls group. Adenovirus and astrovirus obtained from stool of Iranian children with AGE [11][12][13][14][15][16][17][18][19][20][21]. Saderi et al reported the incidence of enteric adenoviruses in Iranian children.…”
Section: Introductionmentioning
confidence: 99%
“…6.7% of stool specimens contained enteric adenoviruses (3.3% Ad40 and 3.4% Ad41) and 2.0% nonenteric adenoviruses [14]. In countries such as Iran, which rotavirus vaccination in not used knowledge of viral ethnological pathogens of AGE is very important in planning diarrhea disease control strategies [15][16][17][18][19]. It might be useful for future vaccine development in the region.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation